The Long-Term Consequences of the Irish Marriage Bar - Irene Mosca; Robert E. Wright (Institute of Labor Economics (IZA), 2019)
A Marriage Bar is the requirement that women in certain jobs must leave that job when they marry. Ireland had a Marriage Bar in place until the 1970s. In 2014/2015, women participating in the The Irish Longitudinal Study on Ageing were asked - for the first time in a nationally-representative survey - specific questions about their experience of the Marriage Bar. In this paper, we use the information from the TILDA respondents for two purposes. The first is to investigate the extent of the Marriage Bar in Ireland. Our analysis suggests that the Marriage Bar was widespread and not confined to specific sectors or occupations (such as the Civil Service). The second purpose is to investigate the long-term consequences of the Marriage Bar. We do so by comparing the outcomes of women who were affected by the Marriage Bar with the outcomes of women who were not affected by the Marriage Bar. Regression analysis shows that women affected by the Marriage Bar have shorter working lives, lower individual income but higher wealth at present, more children and more educated children. However, there are no statistically significant differences in the current health status of the two groups of women. The differences in long-term outcomes do not appear to be confounded by the endogeneity of marriage, education, employment and occupational choices.
Keywords: J71; J78; J24; 330; Marriage Bar; Ireland; discrimination